Inter-relações no crescimento de Araucaria angustifólia (Bertol.) Kuntze em diferentes locais do Rio Grande do Sul - Hess, André Felipe (2006)
This study had as objective to compare the Araucaria angustifolia (Bertol.) Kuntze growth in three different places in Rio Grande do Sul state (Serra do Sudeste, Encosta Superior do Nordeste e Planalto Médio) in diameter, height and volume in function of age for each place and for the three places grouped, to establish the specie development behavior and the possibility to use suitable equations in each place. The data allowed to do an individualized study from the functions that express the behavior from the main dendrometric variables, using in growth prediction, being chosen the model with the best adjust through statistical weighed value of escores. As an evaluation mode, the specie growth was compared to the three places together, using the regression with dummy variable and through the covariance analysis.The study with dummy variable was done with the objective to select an equation of growth based on the age, for diameter, height and volume, allowing to identify the growth differences. The covariance analysis showed that there are differences in growth for each place, showing a necessity to adjust separated growth equations for each place, to minimize the estimative errors. This analyze showed that for diameter, height and volume there is a level and inclination difference from growth curves, indicating that even the growth and the productive capacity are different in the three studied places. It is possible to prove that Araucaria angustifolia, in Serra do Sudeste, shows a growth pattern similar to the other places, indicating that in this place it is also possible to invest in industrial planting from this specie. The average volume at 60 years was of 0,6866 0,6866 m³/wb in Serra do Sudeste, 0,6656 m³/wb in Encosta Superior do Nordeste and 0,5062 m³/wb in Planalto Médio. The Pearson correlation analysis proved that volume showed positive correlation with relative air humidity (0,671), altitude (0,757), clay amount (0,79), organic matter (0,847) and boron (0,974). These Pearson correlation high values indicate the importance of these environmental factors in Araucaria angustifolia growth, as well as give the elements that a regression model should have, where environmental variables in a study of araucaria growth should be used. With these results, regression equations were modeled to annual periodic increment in volume, related to environmental factors, due to stepwise factors, obtaining a good determination coefficient adjust. The increment was used, because it expresses the real growth for a determined period of time. It was proved that annual average increment suffers the influence of environmental factors, varying joined with these. The factors that most influenced were: atmospheric pressure, maximum average temperature, absolute maximum, humidity, insolation and potassium.